PENGARUH INFLASI, KURS, SUKU BUNGA SBI, DAN PERTUMBUHAN PRODUK DOMESTIK BRUTO TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA - Irawan, Kevin Adi (Universitas Slamet Riyadi, 2015)
The purpose of this study was to analyze the effect of inflation, exchange rates, interest rates SBI, and gross domestic product growth partially on stock price index (CSPI). The results obtained can be concluded: Testing the significance of the effect of inflation on the Composite Stock Price Index in Indonesia Stock Exchange 2010 - 2013 obtained t value of 0,759 with a probability value of 0,464 > 0,05 means that there is no significant effect of inflation on the price index Composite. Testing the significance of the effect of the exchange rate (exchange rate) (X2) of the Composite Stock Price Index in Indonesia Stock Exchange 2010 - 2013 obtained t value of -1,966 with a probability value of 0,075 > 0,05 means that there is no significant effect exchange rate (exchange rate) (X2) on Composite Stock Price Index. Testing the significance of the effect of interest rates on Composite Stock Price Index in Indonesia Stock Exchange 2010 - 2013 obtained t value of -0,542 with a probability value of 0,075 > 0,05 means that there is no significant influence of interest rates (X3) against Composite Stock Price Index. Testing the significance of the effect of the gross domestic product of the Composite Stock Price Index in Indonesia Stock Exchange 2010 - 2013 obtained t value of 7,647 with a probability value of 0,000 < 0,05 means that there is a significant effect of the gross domestic product of the Composite Stock Price Index. Keywords: inflation, exchange rates, interest rates SBI, growth in gross domestic product and JCI